TINDAKAN SOSIAL EKONOMI DALAM PERSPEKTIF NEW INTERNATIONAL SOCIOLOGY - Mahendro, Yudo A. (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
This writing tries to explore the social action in the perspective of New International Sociology. In the literature that social action in the relation of economy has three kinds of Phenomena i.e  economic phenomena, economically relvant phenomena, and economically conditioned phenomena. The perspective of economically conditioned phenomena has relation with social capital (there are three components)–network structure, trust and reciprocity, and resources–that are associated with but vary in degree and salience for all forms of social capital.